In Vitro Anti-biofilm and Anti-adhesion Effects of Lactic Acid Bacteria Derived Biosurfactants against Streptococcus mutans - Pourhajibagher, Maryam; Bahador, Abbas (Infectious Disorders - Drug Targets, 2025)
IntroductionBiosurfactants are naturally occurring compounds with various applications, biodegradable, non-toxic, and effective in different conditions. This study focuses on the extraction and evaluation of biosurfactants produced by five strains of lactic acid bacteria (LAB) for their potential to inhibit biofilm formation and adhesion by Streptococcus mutans.MethodsThe strains of LAB-producing biosurfactants such as Lactobacillus salivarius, L. acidophilus, L. plantarum, L. casei, and L. rhamnosus were confirmed by the hemolysis test. The presence of biosurfactants derived from LAB strains and their molecular composition were confirmed, and their cellular toxicity, minimum inhibitory concentration (MIC), and minimum bactericidal concentration (MBC) were investigated. Ultimately, the anti-biofilm and anti-adhesive activities of LAB-derived biosurfactants against S. mutans were determined. Eventually, the effect of biosurfactants on the changes in gene expression associated with biofilm formation of S. mutans was assessed.All the LAB strains used in this study were biosurfactant producers. The LAB-derived biosurfactants exhibited no cytotoxicity towards the human gingival fibroblast (HGF) cell line. According to the results, the lowest and highest MIC values were observed in the biosurfactants derived from L. rhamnosus and L. plantarum at 0.78 mg/mL and 6.25 mg/mL, respectively. The MBC values for the biosurfactants derived from L. rhamnosus, L. casei, L. salivarius, L. acidophilus, and L. plantarum were 3.12, 3.12, 6.25, 12.5, and 12.5 mg/mL, respectively. The LAB-derived biosurfactants at MBC concentrations exhibited significant inhibitory effects on biofilm formation and adhesion of S. mutans (P<0.05) The highest anti-biofilm and anti-adhesion activities were attributed to the biosurfactants derived from L. plantarum, which were not significantly different from the 0.2% chlorhexidine as a positive control group (P>0.05). Moreover, all biosurfactants could significantly decrease the gene expression level of gtfB (P>0.05).ResultsThe study found that LAB-derived biosurfactants exhibit significant anti-adhesion and anti-biofilm activities against S. mutans without any observed cellular toxicity towards HGF cells.ConclusionThese promising bioactive compounds can be utilized as natural antimicrobial agents and biofilm inhibitors to prevent microbial biofilm formation and adhesion in various dental applications, offering a safe and effective alternative for controlling dental biofilms and improving oral health outcomes.
Keywords: lactic acid bacteria